Prarancangan Pabrik Asam Fenil Asetat dari Benzil Sianida dan Asam Sulfat Kapasitas 2.000 ton/tahun - Anggraini, Wulan Fitri; , Ir. Nur Hidayati, M.T., Ph.D (2017)
Phenyl acetic acid plant was established to meet the needs of phenyl acetic acid in the country and abroad. It is based on the availability of raw materials and the needs of phenyl acetic acid in some industrial sectors. Phenyl acetic acid plant with raw material benzyl cyanide and sulfuric acid planned to be established in the Tangerang area with a capacity of 2,000 tonnes per year. In the process, sulfuric acid and water undergoes mixing in the mixer, which is then fed to the reactor. The reactor used is a stirred tank reactor Flow (RATB) to the operating conditions of the reaction at 100 ° C with a pressure of 1 atm, is exothermic, non isothermal adiabatic. Phenyl acetic acid as the main products and the residual reactants are separated from ammonium hydrogen sulfate in a filter press. Then there will be a separation between the organic and inorganic compounds in the decanter. Once out of the decanter, the material will be supplied to the tower distiliasi. The top result of the distillation tower will be fed back into the reactor for recycle, while the bottom results will be fed to the prilling tower (tower granulator) for kristalkan. Then the crushed product to its size becomes smaller in the ball mill, and filtered on a screen that size can be uniform. After a uniform size, the product will be stored in the warehouse. Utility requirements in each year in the form of process water needs as much as 72.3453 kg / h, for cooling water as much as 19125.8813 kg / hour, steam providers as much as 305.3654 kg / hour. 141.3224 kW and electricity as much fuel as 0.0211 m3 / h. The factory is planned to operate for 330 days. Economic analysis indicates the amount of Rp 348,092,560,233.61 fixed capital and working capital of Rp 61,102,148,950.56. While profit before tax of Rp 80,543,222,890.54 and the profit after tax of Rp 56,380,256,023.38. Percent Return on Investment (ROI) before tax amounted to 23.01% and 16.10% after tax. Pay Out Time (POT) before tax and after tax of 3.03 years 3.83 years. Break Event Point (BEP) amounted to 47.5% and Shut Down Point (SDP) amounted to 21.60%. Thus it is feasible to set up factories.